488 hand surgeries with local anesthesia with epinephrine, without a tourniquet, without sedation, and without an anesthesiologist - Sardenberg, Trajano [UNESP]; Ribak, Samuel; Colenci, Ricardo [UNESP]; Campos, Rafael Barcellos de; Varanda, Denis [UNESP]; Cortopassi, Andrea Christina [UNESP] (Sociedade Brasileira de Ortopedia e Traumatologia, 2018)
Objectives: Evaluate the incidence of digital infarction and tissue necrosis using local anesthesia with 1% lidocaine and 1:100,000 epinephrine in wrist, hand, and fingers surgeries, without tourniquet, without sedation, and without an anesthesiologist. Methods: Patients with wrist, hand, and fingers disorders underwent prospectively surgery under local anesthesia with 1% lidocaine and 1:100,000 epinephrine. We evaluated as primary outcomes were the presence of digital infarction and tissue loss due to necrosis. As secondary outcomes, we evaluated the need for the use of sedatives, tourniquet, anesthesiologist assistance, or surgery suspension were evaluated. Results: Fifty‐three wrists, 307 hands, and 128 fingers were anesthetized with lidocaine and epinephrine without any complications related to epinephrine. No patients presented There was no patient that presented with any of the primary or secondary outcomes. Conclusions: Wrist, hand, and fingers surgeries can be safely performed with local anesthesia with 1% lidocaine and 1:100,000 epinephrine, without sedation, without tourniquet, and without an anesthesiologist.

RESUMOObjetivo: Avaliar a incidência de infarto digital e necrose tecidual com o uso de anestesia local com lidocaína a 1% e epinefrina a 1:100.000 nas cirurgias do punho, mão e dedos, sem torniquete, sem sedação e sem anestesista.Métodos: Pacientes com afecções do punho, mão e dedos foram prospectivamente operados com anestesia local com lidocaína a 1% e epinefrina a 1:100.000. Os desfechos primários avaliados foram infarto digital e perda tecidual devido a necrose. Os desfechos secundários avaliados foram necessidade de sedação, torniquete, auxílio de anestesista ou suspensão da cirurgia.Resultados: Foram anestesiados 53 punhos, 307 mãos e 128 dedos com lidocaína e epinefrina sem complicação relacionada à epinefrina. Nenhum paciente apresentou desfechos primários ou secundários.Conclusão: Cirurgias do punho, mão e dedos podem ser feitas de forma segura com anestesia local com lidocaína a 1% e epinefrina a 1:100.000, sem sedação, sem torniquete e sem médico anestesista, com segurança.
488 cirurgias da mão com anestesia local com epinefrina, sem torniquete, sem sedação e sem anestesista
Keywords: Epinephrine; Local anesthesia; Wrist; Hand; Finger; Epinefrina; Anestesia local; Punho; Mão; Dedo